ANALISA DISTRIBUSI DOSIS PADA FANTOM HOMOGEN DAN INHOMOGEN DENGAN SIMULASI MONTE CARLO - Sitti Yani (Komunikasi Fisika Indonesia, 2022)
Monte Carlo simulation with electron gamma shower (EGSnrc) code can produce 3-dimensional dose distribution data. The percent depth dose curve (PDD), dose profile, and isodose curve can be extracted through this 3-dimensional data. In this study, a photon source with an energy of 2 MeV is placed at the source to surface distance (SSD) from the phantom surface by adjusting the collimator aperture which is used to control the size of the exposure field. The SSD distance was varied at a distance of 50 cm, 70 cm, 80 cm, 90 cm, and 100 cm. The size of the exposure area is also varied by 2 × 2 cm2, 5 × 5 cm2, 7 × 7 cm2, and 10 × 10 cm2. The dose distribution analysis was carried out on homogeneous phantoms containing water and inhomogeneous phantoms containing tissue/bone/lung/bone/tissue material. The PDD curve and dose profile represent dose changes with depth and x or y direction, respectively. The PDD curve on a homogeneous phantom shows an increase in the value on the surface of the phantom to the depth with the maximum dose. This curve then decreases gradually with increasing depth. Inhomogeneous ghosts show spikes in the border region of the two media with different densities. This is due to the contribution of the backscattered electrons generated by the bone media and into the tissue media. This phenomenon is also seen in the isodose curve for inhomogeneous phantoms.